PERSEPSI KONSUMEN TERHADAP BAURAN PEMASARAN PADA PRODUK DAGING SAPI SEGAR DI WARUNG PANGAN SEHAT KOTA BOGOR - Hari Subagyo, Wawan; Widiyastuti, Ari (Economicus, 2020)
The purpose of this study was to determine how consumers' perceptions of the marketing mix of fresh beef products at Warung Pangan Sehat. This type of research uses descriptive quantitative. The sampling technique used is accidental sampling technique. Determination of the sample using the Slovin formula so that the sample obtained is 100 respondents. And data analysis techniques using the tools SPSS and WMS.Based on the results of the analysis discussion using the Weight Mean Score (WMS). The results of the assessment of the condition of each variable, namely the criterion product variable are very good with an average value of 3.48, the criteria promotion variable is very good with an average value of 3.42, the criteria price variable is very good with an average value of 3.35, the location variable very good criteria with an average value of 3.31. The highest average interpretation value is on the product variable with a value of 3.48 which is in the very good interpretation criteria. Consumers have perception that fresh beef products at Warung Pangan Sehat are very good. While the lowest average interpretation value is on the location variable with a value of 3.31 which means that the interpretation is very good. Consumers have a perception that the location of Warung Pangan Sehat is still accessible to consumers. The average interpretation value of all indicators is 3.39 which means very good. Overall, consumer perceptions of fresh beef products and promotions carried out are very good, the prices offered and the locations of Warung Pangan Sehat are affordable to consumers.